RELEVANSI MANAJEMEN SUMBER DAYA MANUSIA DALAM LEMBAGA DAKWAH - Imam Saparudin; Muhibuddin Muhibuddin; Siti Nuri Nurhaidah; Mudrika Mudrika; Muhammad Yudi Ali Akbar (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi Islam Institut Agama Islam (IAI) Al-Azhaar Lubuklinggau, 2025)
In conducting da'wah, whether under the direction of another body or independently, education or training for Da'i is very important. As a conveyor of da'wah to the target group, da'i are obliged to carry out their duties professionally. Therefore, based on these arguments, it is important to obtain qualified or professional Da'i. This means that da'wah cannot just happen, it is not a simple act. Thorough planning is required before conducting da'wah, including placing people according to their respective fields of expertise. It is important for a Da'i to have the necessary skills to carry out their duties in the field of Da'wah. The results of this study emphasize the relevance of effective Da'wah competencies and Da'wah to the success of Da'wah organizations. This includes the ability to lead organizations effectively because they have technical, human, and conceptual skills, as well as the ability to apply and expand their mindset in Sharia administration